Prolonged Static Whole-Body Roll-Tilt and Optokinetic Stimulation Significantly Bias the Subjective Postural Vertical in Healthy Human Subjects - Wedtgrube, Andrea; Bockisch, Christopher J.; Straumann, Dominik; Tarnutzer, Alexander A. (Frontiers in Neurology, 2020)
Background: Prolonged static whole-body roll-tilt has been shown to bias estimates of the direction of gravity when assessed by static paradigms such as the subjective visual vertical and the subjective haptic vertical. Objective: We hypothesized that these shifts are paradigm-independent and thus predicted a post-tilt bias as well for self-adjustments along perceived vertical (subjective postural vertical, SPV). Likewise, rotatory optokinetic stimuli, which have been shown to shift the SPV when presented at the time of adjustments, may have an lasting effect on the SPV, predicting a shift in the perceived direction of gravity in the direction of the optokinetic rotatory stimulation. Methods: Self-adjustments along perceived vertical by use of a motorized turntable were recorded at baseline and after five minutes of static whole-body roll-tilt (orientation=±90°, adaptation period) in ten healthy human subjects. During adaptation subjects were either in darkness (no OKN stimulation) or were presented a full-field rotatory optokinetic stimulus (velocity=±60°/sec). Statistical analysis of adjustment errors for the different conditions was performed using a generalized linear model. Results: After five minutes of static whole-body roll-tilt in darkness, we observed significant (p<0.001) shifts in the SPV averaging -2.8° (adaptation position: -90°) and 3.1° (+90°), respectively. Adding an optokinetic rotatory stimulus resulted in an additional, significant shift of SPV adjustments towards the direction of the previously presented optokinetic rotation (optokinetic clockwise rotation: 1.4°, p=0.034; optokinetic counter-clockwise rotation: -1.3°, p=0.037). Trial-to-trial variability of turntable adjustments was not significantly affected by adaptation. Conclusions: Prolonged static roll-tilt results in a significant post-tilt bias of the perceived direction of gravity when assessed by the SPV, confirming previous findings from other vision-dependent and vision-independent paradigms. This finding emphasizes the impact of recent whole-body roll orientations relative to gravity. Such adaptational shifts in verticality estimates may be explained in the context of Bayesian optimal observer theory with a bias of prior knowledge (i.e., expectation biased by experience). Our findings also have clinical implications, as the observed post-tilt bias may contribute to postural instability when standing up in the morning with an increasing risk for falls and fall-related injuries in humans with preexisting balance disorders.